(untitled) (Papeles, 2025)
Introduction: Competency-based assessment is a process that allows for valuing and reflecting upon the ideal performance of a future professional in specific contexts, integrating diverse knowledge to face real learning situations. In this sense, the present article is framed within a theoretical-reflective approach to competency-based assessment, conceived as a path towards comprehensive and authentic training in higher education, specifically at the Universidad Pedagógica Experimental Libertador in Venezuela. Its purpose is to shed light on the educational realities that can emerge from the implementation of this innovative approach in that university context. Methodology: The study was framed within the interpretative paradigm, under a qualitative methodological perspective, in a documentary review. Diverse recent academic literature was analyzed, including scientific articles, books, and official documents, which allowed for revealing and interpreting competency assessment as a comprehensive and authentic process. Results and Discussion: The findings that emerged after the review of various sources refer to the great relevance of the competency assessment approach in education, in addition to showing the transition between objectives and competencies, and the transcendental changes generated in educational stakeholders as a result of comprehensive training. Conclusions: This approach establishes some reflections in the search to make known the changes that must inevitably emerge from competency-based student performance assessment in higher education institutions.